2014
DOI: 10.3109/09638288.2014.935494
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation therapies for older clients of the Ontario home care system: regional variation and client-level predictors of service provision

Abstract: Where a client lived was an important determinant of service provision in Ontario, raising the possibility of inequities in access to rehabilitation services. Health care planners and policy makers should review current practices and make adjustments to meet the increasing and changing needs for rehabilitation therapies of the aging population. Implications for Rehabilitation For older adults in home care, the goal of rehabilitation therapy services is to allow individuals to maintain or improve physical funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…This finding was expected due to the longer life expectancy of women in Turkey. While this result was consistent with the findings of several previous studies, [12][13][14][15] some other studies reported conflicting results. [16][17][18][19] We found significant difference between years in terms of use of home health care services.…”
Section: Discussionsupporting
confidence: 68%
“…This finding was expected due to the longer life expectancy of women in Turkey. While this result was consistent with the findings of several previous studies, [12][13][14][15] some other studies reported conflicting results. [16][17][18][19] We found significant difference between years in terms of use of home health care services.…”
Section: Discussionsupporting
confidence: 68%
“…A recent systematic review also identified that both patient and facility factors lead to increased readmissions after hip fracture [30]. International reports support improved patient outcomes from discharge to rehabilitation facilities, but at a higher direct cost than discharge to home [15,19,33,35,47].…”
Section: Discussionmentioning
confidence: 99%
“…Recovery after hip fracture is prolonged extending over at least the first year, well beyond the care delivered in the surgical hospital setting [12][13][14]. There is growing recognition that care delivery in the post-acute period, including where patients are discharged to after the surgical hospital stay, is under-studied and whose impact on patient recovery and health services utilization is unclear [15][16][17][18][19][20][21][22][23][24][25]. We hypothesized that, in Canada, hospital type (teaching versus community) might affect discharge decision-making with teaching hospitals more likely to send patients to other sites for further recovery (i.e., rehabilitation or acute care) due to surgical bed demands and availability of community-based care.…”
Section: Introductionmentioning
confidence: 99%
“…Seven relatively homogeneous subgroups: dependent and immobile clients with cognitive problems; dependent but mobile clients with cognitive problems; primarily women requiring assistance with IADLs and some ADLs; primarily women requiring assistance with independent activities of daily living (IADL); clients requiring assistance with IADL and bathing, activities of daily living (ADL); independent cognitively intact younger clients; and clients who lived alone and required some assistance with housework and bathing) that differed on characteristics such as age, sex, cognition, and functional impairment. Armstrong et al, 2015 Observational study -Ontario 299,262 older long-stay home care clients…”
Section: Older Adult Client-level Predictorsmentioning
confidence: 99%